METHOD OF TEACHING ENGLISH WRITING IN THE SECOND SEMESTER OF ENGLISH AT ISLAMIC UNIVERSITY OF MALANG - Fizi, Ridhani (Darussalam, 2023)
ABSTRACTThe present study aims at describing the teachers’ method of teaching English writing in the second-semester students of English at Islamic University of Malang, which covers teaching procedures, writing material selection, and the use of instructional media. It also aims at finding the students’ perception of their teachers’ method of teaching writing.Besides the writing teachers of English, teaching method also plays a significant role in writing class since without a method the teachers will not be able to achieve the desired of learning. In writing instruction, there are many methods that can be applied by the writing teachers.This study used the descriptive design. The data were collected through observation, interview, questioners, and documentation and analyzed using a guideline analysis, while the data of the students’ questioners were analyzed using tally system to find the percentage.The subjects of this study consisted of two teachers and their students of English department at Islamic University of Malang. There are 25 students of class C and 23 students of class B.The findings showed that in general, the method of teaching writing applied by the two teachers of writing in Second Semester of English at Islamic University of Malang was in line with the theory of writing instruction, especially that proposed by the Community Language Learning Method. In general, the teaching procedures of the two writing teachers could be considered very good because they used various techniques in teaching writing. Their selection of writing material could be considered very good because they took the writing material from textbook and other resources. Their use of instructional media could be considered good, because the two teachers used two instructional media; whiteboard and its marker, and some pictures from newspapers.The other finding was the diary assignment done by one of the two classes, The students did it every day out of class during the semester. The purpose of this activity was to get students used to write and to make them practice the theory they had learned. Therefore, this activity could be considered very good. And the students’ perception of their teacher’s method of teaching was positive. The teacher successfully made students motivated.Based on the findings, it is suggested that teachers of writing should not use only one method, but also other methods with more variations in the teaching procedure, material selection, and the use of instructional media. In selecting the writing material, it is suggested that they select various writing materials. Because of the importance of instructional media, it is suggested that teachers of writing use and prepare them well. For the second-semester students of English at Islamic University of Malang, it is suggested that they are more independent and active in learning writing.Key words: teaching, methods, English, writing